EFFECTS OF ACUPUNCTURE ON RHEUMATOID ARTHRITIS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Li, Jing; Yang, Jie; Wu, Song; Wang, Ming-Rui; Zhu, Ji-Min (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of this study was to evaluate the efficacy of acupuncture for treating rheumatoid arthritis (RA). Materials and Methods: The literature were searched using 6 databases, including Pubmed, Embase, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, VIP and Wanfang database up to December 2013, without language restrictions. All randomized clinical trials (RCTs) comparing acupuncture treatment with non-acupuncture treatment of RA was considered. Methodological quality was assessed using the Jadad score. Results: After strict screening, a total of 21 studies containing 1772 participants were included. The meta-analysis indicated that a significant benefit of acupuncture compared with non-acupuncture on improving the symptoms of RA (pooled RR = 1.19, 95% CI 1.08–1.31, Z = 3.47, P = 0.001). In the subgroup analysis, 9 RCTs showed significant effects of acupuncture for response rate compared with western medicine (RR = 1.26, 95% CI 1.02–1.55, Z = 2.19, P = 0.028); 5 RCTs showed significant effects of acupuncture plus traditional Chinese drug compared with traditional Chinese drug (RR = 1.17, 95% CI 1.07–1.29, Z = 3.31, P = 0.001); 5 RCTs showed beneficial effects of acupuncture plus western medicine compared with western medicine (RR = 1.27, 95% CI 1.06–1.53, Z = 2.56 P = 0.01). Conclusion: This meta-analysis demonstrates that acupuncture may have a favorable effect on treating RA. However, the evidence was limited by the small sample size and the low methodological quality. Considering the potential of acupuncture, more researches and well-designed, rigorous and large clinical trials are needed.